Hungarian Higher Education (Training and Practice : Journal of Educational Sciences, 2010)
Present article is to examine how Hungarian higher education has reached its present state, what reasons there have been for expansion. I start my historical and cultural look back in the middle ages not only concentrating on higher education, rather on education in general, as its changes have had an influence on its integrated part, tertiary education. The aim of this study is to describe the situation of Hungarian higher education mainly focus on increased number of students. In the centre of relevant discussions stand the question of expansion and its consequences, acceptance or refusal and the possibilities of its reverse. After giving a short historical background the topic is treated by literature, statistics, data referred to demography, labour market, economic and social processes and its opposite views.